Exploring the Link between Acne Vulgaris Severity and Adolescents' Quality of Life in Gresik - Amalia, Rizki Nur; Zuhroh, Diah Fauzia; Ernawati, Ernawati; Sari, Diah Jerita Eka (Universitas Muhammadiyah Gresik, 2024)
Background :Adolescence is a transition period between childhood and adulthood, this creates conflict within adolescents which often gives rise to strange and awkward behavior, this is because during adolescence there is a period of puberty which can change physically and psychologically. So the appearance of acne vulgaris can disrupt teenagers' self-confidence. The aim of the study was to analyze the relationship between the severity of acne vulgaris and the quality of life of adolescents. Research design :The research design used is correlation research using a cross sectional approach. The population design used was teenagers in Gresik, the sample size was 210 teenagers, with a sampling technique using simple random sampling. Data collection used the CADI questionnaire and observation sheets. The variables measured were the severity of acne vulgaris and the quality of life of adolescents. Data analysis used cross tabulation and sperm rank test. Research result : Of the 210 students at SMAN who experienced mild degrees (46.2%), moderate degrees (45.2%), severe degrees (8.6%). Half of teenagers experience mild degrees. And regarding the quality of life of students and students who had no disturbances (1.0%), mild disturbances (25.7%), moderate disturbances (31.9%), severe disturbances (41.4%), half of the respondents experienced severe disturbances. The results of the Spearman rank test are p = <0.05, meaning there is a significant relationship. Conclusion : There is a relationship between the severity of acne vulgaris and the quality of life of adolescents in Gresik. Keywords: Acne Vulgaris, Quality of Life, Adolescents